Urgensi Pemanfaatan E-Marketing dan Self Directed Learning Dalam Meningkatkan Kinerja UMKM selama masa pandemi covid-19 di Kabupaten Boalemo - Hasmirati Hasmirati; Hamsir Saleh; Alfin Akuba (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This research was conducted to determine the effect of the Urgency of Using E-Marketing and Self Directed Learning in Improving MSME Performance during the Covid-19 pandemic in Boalemo Regency. Samples were taken using a purposive sampling technique, namely determining a sample based on certain criteria. This research uses quantitative methods. The data analysis technique used in this research is multiple linear regression analysis technique. The results obtained from this study are that the use of E-Marketing and Self Directed Learning together has a significant effect on MSME performance. of 0.000. Utilization of E-Marketing partially has a significant effect on MSME performance of 0.000. While Self Directed Learning partially has a significant effect on MSME performance of 0.001